Expansion of dynamic range of sampling and storage device by weight integration of narrow-band oscillation - B. D. Zhenatov (Омский научный вестник)
The most bottleneck of high-frequency digital radio receivers in terms of dynamic characteristics is the process of analog-to-digital conversion. Most often, to meet the requirements for the speed and dynamic range of the analog-to-digital conversion, a sampling and storage device (UHF) is included in front of the analog-to-digital converter (ADC), which is significantly simpler in structure than the ADC structure, but reduces the requirements for its speed and dynamic range [1, 2]. A method for expanding the dynamic range of the integrating sampling and storage device for digital radio receivers using the weight integration of the input narrow-band oscillation is proposed.